Topical oxygen therapy & micro/nanobubbles: a new modality for tissue oxygen delivery. Issue 3 (5th January 2018) - Sayadi, Lohrasb R; Banyard, Derek A; Ziegler, Mary E; Obagi, Zaidal; Prussak, Jordyne; Klopfer, Michael J; Evans, Gregory RD; Widgerow, Alan D
Abstract : Up to 15 billion dollars of US health care expenditure each year is consumed by treatment of poorly healing wounds whose etiologies are often associated with aberrancies in tissue oxygenation. To address this issue, several modes of tissue oxygen delivery systems exist, including Hyperbaric Oxygen Therapy (HBOT) and Topical Oxygen Therapy (TOT), but their efficacies have yet to be fully substantiated. Micro/nanobubbles (MNBs), which range anywhere from 100 μm to <1 μm in diameter and are relatively stable for hours, offer a new mode of oxygen delivery to wounds. The aim of this article is to systematically review literature examining the use of TOT for wound healing and use of MNBs for tissue oxygenation using the MEDLINE database. The search yielded 87 articles (12 MNB articles and 75 TOT articles), of which 52 met the inclusion criteria for this literature review (12 MNB articles and 40 TOT articles). Additionally, we present an analysis on the efficacy of our MNB generating technology and propose its use as a wound healing agent.